BYRD STATION SNOW TUNNELS - MAINTENANCE EQUIPMENT AND TECHNIQUES. - Sherwood, G. E.; Gifford, S. E. (1965)
To prevent excessive snow-tunnel closure, equipment and techniques were developed to score and trim the snow-tunnel walls at Byrd Station Antarctica. The equipment includes a chain saw and guide for scoring the snow to a controlled depth, hand tools for chipping the scored snow from the walls, a gasoline-fired snow melter for melting the waste snow, and a pump and hoses for transferring the water to the station sewer line. This equipment was tested at Byrd Station in January 1965 and found to be suitable for clearing walls with up to 7 inches of closure. Less frequent clearing would be possible if side-cutting equipment were used to remove the snow. (Author)